OPTIMIZED BROADBAND WILKINSON BALUN - DESIGN AND ANALYSIS USING METAMATERIAL (International Journal of Engineering and Computer Science, 2013)
The design presented here mainly focuses on implementation of a broadband Wilkinson balun using composite right/left-handed (CRLH) transmission line. This has its components, namely Wilkinson power divider (WPD), microstrip phase shift line and CRLH unit cell along with interdigital capacitor, which forms base of the unit cell. The designing and implementation of WPD, CRLH unit cell and Interdigital Capacitor (IDC) has been done using HFSS 13.0. Results of proposed balun are discussed and compared with broadband Wilkinson balun using purely left handed transmission line (PLHTL). A balun is designed using the same. Compactness, losses and phase response are the key issues in microstrip balun design and are dealt with, for best output. The design idea for this balun was taken from [8] and in this paper the design is implemented with a new more compact unit cell and instead of using two quarter wave bridges at two output lines each, total of λ/8 lines are added in each branch this reduces the size to much extent. The final design has been optimized using HFSS 13.0 for best trade-off between losses and phase response. The presented balun has been optimized for best trade-off between losses and phase response, which is key part of a balun design. Bandwidth achieved is 2.75 GHz, with fractional bandwidth of 122%